PROGNOSTIC BIOMARKER OF INVASIVE BREAST CANCER ANALYSIS AND MOLECULAR INTERACTION WITH Taxus sumatrana PHYTOCOMPOUNDS - Muhammad Faisal; Riyanda Indrawan Sani (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
Invasive breast cancer remains a leading cause of cancer mortality, requiring reliable prognostic biomarkers and new therapeutic agents. Taxus sumatrana contains bioactive compounds with potential anticancer activity. We aimed to analyze gene expression data and identify the worst prognostic of invasive breast cancer as well as analyzing molecular interaction with compounds of T. sumatrana. Gene expression analysis data was conducted by mining transcriptomic and Kaplan-Meier data from the UALCAN database to compare breast tumor and normal tissues and evaluated survival among 100 candidate genes. PGK1 was selected based on high expression and poor prognosis. Subsequently, 31 compounds of T. sumatrana from the KNApSAcK database were subjected to molecular docking against PGK1. PGK1 demonstrated significantly stronger expression in primary tumor tissues than normal tissues. This expression was associated with the poorest survival trend among analyzed biomarkers (TAGLN2, TUBA1B, and COX7B), indicating its prognostic relevance. Taxinine B, Tasumatrol X, and Tasumatrol U were identified as promising compounds according to their favorable binding affinities toward the active site of PGK1, forming hydrogen bonds and hydrophobic interactions at key residues. PGK1 is a promising poor prognostic biomarker and therapeutic target in invasive breast cancer. Taxinine B from T. sumatrana may act as potential PGK1 inhibitors and merit further experimental validation.